Managing information resources in libraries : - Clayton, Peter (Facet Publishing, 2009)
The management of information resources in libraries is of greater importance in the digital world. This book encompasses different areas of collection management and cover topics, such as: collection management in the organizational context; collection development policies; selection principles and resources; budget management; and more